1990
DOI: 10.1039/c39900001707
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-catalysed hydrolysis of an unactivated amide. Application of the groves' rule to the hydrolysis of acrylamide

Abstract: Conjugate addition of N-benzyl-N',N'-dimethylethylenediamine to acrylamide affords a chelating amide in which the amide carbonyl can coordinate to the bound metal only via a six-membered chelate; this compound demonstrates copper(i1)-catalysed amide hydrolysis, in which each metal acts on at least five equivalents of substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The rate of amide hydrolysis, in which the limiting step is believed to be breakdown of the tetrahedral intermediate [64] , may depend critically upon stereoelectronic constraints of the metal and the carbonyl ligand [64] , [68] , a nearby amino acid side chain for proton transfer to the leaving amide nitrogen [66] , as well as the identity of the attacking nucleophile. Hence, post-translational modifications, familial mutations, binding partner or receptor interactions in vivo , or formation low molecular weight oligomeric species may modulate such a process.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of amide hydrolysis, in which the limiting step is believed to be breakdown of the tetrahedral intermediate [64] , may depend critically upon stereoelectronic constraints of the metal and the carbonyl ligand [64] , [68] , a nearby amino acid side chain for proton transfer to the leaving amide nitrogen [66] , as well as the identity of the attacking nucleophile. Hence, post-translational modifications, familial mutations, binding partner or receptor interactions in vivo , or formation low molecular weight oligomeric species may modulate such a process.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of unactivated peptide bonds is exceptionally slow at physiological pH (the half-life of a typical peptide bond is 7-350 years at neutral pH and 25°C) [25,26,27], although this can be efficiently catalyzed by enzymes [28,29]. To understand the mechanism of these remarkable hydrolysis reactions, and to mimic enzymatic processes, many studies have been carried out over several decades using a variety of model complexes of Cu(II) [7,8,9,30,31,32,33,34,35 (recent papers)], Zn(II) [22,34,35], Ni(II) [34,35], Pd(II) [10,11,12,13,14,15,16,17], Pt(II) [10,17,18], Co(III) [36, 37, 38 (recent papers)] and Ce(IV) [21,23]. However, the hydrolysis of unactivated peptides promoted by substitution-labile bivalent metal complexes such as Ni(II), Cu(II) and Zn(II) is generally too slow for detailed kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydrolysis of unactivated peptides promoted by substitution-labile bivalent metal complexes such as Ni(II), Cu(II) and Zn(II) is generally too slow for detailed kinetic studies. Therefore, activated amides have often been used to investigate reaction mechanisms, instead of peptides themselves [4,5,30,31,32,33,34,35,36,37,38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…that can serve as nucleophiles. A number of investigators have concluded that nucleophilic attack by metalhydroxo species is at least partially responsible for observations of metal ion-catalyzed amide hydrolysis (Buckingham et al, 1970;Duerr and Czarnik, 1990;Takasaki et al, 1993). Mechanism 2 is also observed in systems where the metal ion coordinates a side group of the substrate that can serve as an intramolecular nucleophile (Sigman and Jorgensen, 1972;Groves and Baron, 1989;Koike et al, 1995).…”
Section: Amide and Anilide Hydrolysis: Catalysis And Inhibition By Di...mentioning
confidence: 99%